Associations Between Algae, Substrate Characteristics, and Herbivorous Fish in Coral Reef Ecosystems of Pari Island, DKI Jakarta - Hadiana, Hadiana; Agustinus, Samosir; Eko Cahyo, Hutomo Zudah; Samsur, Mohamad; Ayu Winna, Ramadhani; Dewi Ratih Rizki, Damaiyanti; Santi Kusuma, Fajarwati; Frelyta Ainuz, Zahro (The Egyptian Society for the Development of Fisheries and Human Health (ESDFHH), 2025)
Coral reefs around Pari Island, DKI Jakarta, provide vital habitats supporting corals, algae, and reef fish. This study examined the associations between algal cover, bottom substrates, and herbivorous fish abundance at four sites (South, West, East, and North Pari) during July 2020, October 2020, and January 2021. Using the line intercept transect (LIT) method at depths of 3 and 10m, data on substrate composition, algal types, herbivorous fish, and water quality were collected. Algal cover ranged from 7.23 to 31.48%, with the highest at shallow depths (3m) and during the transitional season (October). Turf algae dominated on dead coral substrates, while macroalgae such as Padina, Sargassum, and Halimeda were common on sandy areas. Correlation analysis showed strong positive relationships between algae and dead hard coral (r= 0.823, P< 0.01) and sand (r= 0.765, P< 0.05), but a weak link with herbivorous fish (r= –0.267, P>0.05). Principal component analysis indicated that macroalgae, herbivorous fish, and dead coral contributed most to ecosystem variation (55.97%). Elevated nitrate levels (0.124mg. L⁻¹) exceeded national standards, promoting algal growth. Nutrient enrichment and substrate conditions, rather than herbivory, were identified as the main drivers of algal proliferation on Pari Island reefs.